2017
DOI: 10.1002/joc.5320
|View full text |Cite
|
Sign up to set email alerts
|

Response of viticulture‐related climatic indices and zoning to historical and future climate conditions in Greece

Abstract: Climate and viticulture are indisputably linked and thus knowledge of the predominant weather and climate conditions of a given area is essential for optimum variety selection, viable production and overall wine quality. In this study, an assessment of the current (1981–2010) and future conditions (2021–2050 and 2061–2090) through principal climatic elements and six bioclimatic indices (i.e. Growing season average temperature, growing degree‐days, Huglin index, biologically effective degree‐days, dryness index… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
52
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 53 publications
(58 citation statements)
references
References 35 publications
5
52
0
1
Order By: Relevance
“…The expected warming and drying results in shifts of the DO/sub‐regions to higher classes. These results are in agreement with the warming and dryness reported in other southern European countries (e.g., Duchêne and Schneider, ; Neumann and Matzarakis, ; Lorenzo et al ., ; Dunn et al ., ; Koufos et al ., ).…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…The expected warming and drying results in shifts of the DO/sub‐regions to higher classes. These results are in agreement with the warming and dryness reported in other southern European countries (e.g., Duchêne and Schneider, ; Neumann and Matzarakis, ; Lorenzo et al ., ; Dunn et al ., ; Koufos et al ., ).…”
Section: Discussionmentioning
confidence: 97%
“…Thus, climate change can bring risks to the quality/characteristics of wine, but also opportunities for cooler regions (Neethling et al ., ) The dependence of grapevine varieties on specific climatic conditions and the perennial nature of grapevines limits the adaptation of the current DO/sub‐regions to climate change (Webb et al ., ; Metzger and Rounsevell, ; Dunn et al ., ). In areas with the most negative impacts, potential adaptations include (a) modifications in vine training and canopy architecture, (b) adjustment of vine practices, for example, irrigation and soil management, (c) moving vine cultivation to new areas at higher elevations and/or to north‐facing slopes, (d) varying wine style preferences (e.g., red or sweet wines as an alternative to white wines) (Koufos et al ., ) or (e) the growth of new grapevine varieties in DOs that have greater adaptability with future warmer and drier climates.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In Australia, Hall and Jones (2009) found that the area with a GST between 13 and 21°C may reduce by up to 50% by 2070, which could result in 21 out of the 61 Australia's recognised wine regions sitting outside the GST limits. Internationally, studies have been conducted in New Zealand (Anderson et al 2012), America (Jones 2005, White et al 2006, Hall and Jones 2009, Diffenbaugh and Scherer 2013, Schultze et al 2016, Schultze and Sabbatini 2019), Canada (Shaw 2017), Europe (Jones and Alves 2012, Neethling et al 2012, Koufos et al 2018) and the United Kingdom (Nesbitt et al 2018), have created a growing body of work which indicates that, as the global air temperature warms, viticultural zones will invariably change. On a global scale, Hannah et al (2013) used GST as a metric to assess the suitability of winegrapes in the future for viticulture and concluded that this might decrease by 25 to 73% in major wine producing regions internationally by 2050.…”
Section: Introductionmentioning
confidence: 99%
“…In Greece, vineyard area under irrigation has been steadily increasing during the last three decades. Moreover, since temperature and rainfall patterns are predicted to change, increasing the risk of drought in Greece's viticultural regions (Koufos et al, 2018), supplemental irrigation will greatly affect the ability of existing varieties to ripen fruit. The aim of this study was to determine and compare anthocyanin content and profile under variable irrigation regimes in four red grape cultivars (Vitis vinifera L.), namely Agiorgitiko and Xinomavro, alongside the well studied French cvs.…”
Section: Introductionmentioning
confidence: 99%